Conflict Resolution in Syair Sultan Maulana - Wan Razali, Wan Roshazli; Abu Bakar, Sakinah (Malay Literature, 2020)
This article discusses the conflicts and resolutions in Syair Sultan Maulana . The researcher aims to prove that works written in the past do not come out of nowhere but are the products of the author's wisdom to deliver a meaningful message through the use of symbols. In the context of this text, the author has applied several ways or methods of conflict resolution used by the local people in the past to ensure continued harmony in their fatherland. Therefore, this article will uses the conflict resolution approach introduced by Abdullah Hassan and Ainon Mohd. This approach lists several methods for resolution, such as cooperation, negotiation, domination, avoidance, integrity, obligation, and compromise. Malay literary works, especially historical ones, usually also deal with the lives of the people at the time. In traditional Malay literary works, many issues are discussed for the benefit of future generations. The most interesting aspects of these classical texts are the conflicts, problems, and disputes occurring in the community at the time, whether they are among the royalty, nobility or ordinary folk. Keywords: Conflict, resolution, syair , historical literature, harmony